Randomized double-blind, placebo-controlled multicenter phase III study of prevention of irinotecan-induced diarrhea by a probiotic mixture containing Bifidobacterium BB-12®Lactobacillus rhamnosus LGG® in colorectal cancer patients - Mego, Michal; Danis, Radoslav; Chovanec, Jozef; Jurisova, Silvia; Bystricky, Branislav; Porsok, Stefan; Konkolovsky, Peter; Vaclav, Vladimir; Wagnerova, Maria; Streško, Marian; Brezinova, Bibiana; Rečková, Mária; et al. (Frontiers in Oncology, 2023)
The incidence of irinotecan-induced diarrhea varies between 60-90%, by which the incidence of severe diarrhea is 20-40%. The objective of this phase III trial was to determine the effectiveness of the probiotic mixture containing Bifidobacterium, BB-12 ® and Lactobacillus rhamnosus, LGG ® in the prophylaxis of irinotecan-induced diarrhea in metastatic colorectal cancer patients due to a reduction in the activity of intestinal beta-D-glucuronidase.From March 2016 to May 2022, a total of 242 patients with colorectal cancer starting a new line of irinotecan-based therapy were registered to the study in 11 cancer centers in Slovakia. Patients were randomized in a ratio 1:1 to probiotic formula vs. placebo that was administered for 6 weeks. Each capsule of Probio-Tec ® BG-Vcap-6.5 contained 2.7x10 9 colony-forming units (CFU) of 2 lyophilized probiotic strains Bifidobacterium, BB-12 ® (50%) and Lactobacillus rhamnosus GG, LGG ® (50%).Results: Administration of probiotics compared to placebo was not associated with a significant reduction of grade 3/4 diarrhea (placebo arm 11.8% vs. probiotic arm 7.9%, p=0.38). Neither the overall incidence of diarrhea (46.2% vs. 41.2%, p=0.51) nor the incidence of enterocolitis (3.4% vs. 0.9%, p=0.37) was different in the placebo vs. probiotic arm. Subgroup analysis revealed that patients with colostomy had higher incidence of any diarrhea and grade 3/4 diarrhea in the placebo arm compared to the probiotic arm (48.5% vs. 22.2%, p=0.06 and 15.2% vs. 0%, p=0.06, respectively). Moreover, patients on probiotic arm had significantly better diarrhea-free survival (HR = 0.41, 95%CI 0.18 -0.95, p=0.05) and needed less loperamide (p=0.01) compared to patients on placebo arm. We did not observe any infection caused by probiotic strains used in this study.This study failed to achieve its primary endpoint, and results suggest a lack of benefit of administered probiotic formula for the prevention of irinotecan-induced diarrhea.However, subgroup analysis suggests a possible benefit in patients with colostomy.